Profile Modification for Tilting Coupled with Skew Roller in Cylindrical Roller Bearing - Ma Mingming; Liu Xiaoling; Tian Xiaoyong; Zhao Huimin (Jixie chuandong)
In order to reduce the edge effect,the tilting and skew effect of the roller. Using the Eyring Non- Newtonian fluid model,the parabolic modification function is applied to a finite line contact thermal EHL model. The pressure is solved with multilevel method and the temperature is calculated with sequential column sweeping technique. A special coordinate transformation technology is used for the solving of cylindrical roller skew. For the tilting rollers,the initial value of a dimensionless load offset distance Ew is given,and then the oil film pressure,the film thickness,and the dimensionless moment M are obtained. Moreover,the relative error of torque Err M is calculated,and a new value of the load is obtained simultaneously. when the roller is at the ideal,the tilting,the skew or the tilting coupled with the skew status,the profile modification for the roller generatrix can reduce the edge effect and the tilting or the skew effect. In addition,an optimum value of the profile modification for the roller generatrix exists at the four kinds of status. The optimum value is 9,11,14 and 16 mm at the four status. The method which a profile modification function is added on the straight roller generatrix is simple and feasible. A new idea for the engineering application of the roller profile modification is provided.